Proceedings of 2nd International Conference on Intelligent Computing and Applications ICICA 2015 - Deiva Sundari, P.; Dash, Subhransu Sekhar; Das, Swagatam; Panigrahi, Bijaya Ketan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
Second International Conference on Intelligent Computing and Applications was the annual research conference aimed to bring together researchers around the world to exchange research results and address open issues in all aspects of Intelligent Computing and Applications. The main objective of the second edition of the conference for the scientists, scholars, engineers and students from the academia and the industry is to present ongoing research activities and hence to foster research relations between the Universities and the Industry. The theme of the conference unified the picture of contemporary intelligent computing techniques as an integral concept that highlights the trends in computational intelligence and bridges theoretical research concepts with applications. The conference covered vital issues ranging from intelligent computing, soft computing, and communication to machine learning, industrial automation, process technology and robotics. This conference also provided variety of opportunities for the delegates to exchange ideas, applications and experiences, to establish research relations and to find global partners for future collaboration.
Time-Domain Analytical Modeling of Current-Mode Signaling Bundled Single-Wall Carbon Nanotube Interconnects -- Stability Analysis of Carbon Nanotube Interconnects -- Multi-robot Assembling Along a Boundary of a Given Region in Presence of Opaque Line Obstacles -- Dissimilar Regulatory Actions between Neurodegenerative Disease Pairs through Probabilistic Differential Correlation -- Multiobjective Ranked Selection of Differentially Expressed Genes -- Comfort Sensor Using Fuzzy Logic and Arduino -- Despeckling of Medium Resolution Scansar Data -- Recommendation Based P2P File Sharing on Disconnected MANET -- Smart Plugs for Household Appliances -- Modeling and CFD Analysis of Gerotor Pump -- A Robust Energy Management System for Smart Grid -- Innovation in the Operation of UAV Sensors -- Computational Study of Coil Helical Spring: Automobile clutch -- A Survey on Challenges in Integrating Big Data.
Keywords: Computational intelligence; Signal processing; Control engineering; Robotics; Automation; Computational Intelligence; Signal, Speech and Image Processing; Control, Robotics, Automation